Application of Light Therapy in Brain Function Modulation and Rehabilitation - TAO Qian; SO Kwok-Fai (康复学报)
The discovery of intrinsically photosensitive retinal ganglion cells (ipRGCs) has opened up a new field of research: the non-image forming visual (NIFV) of light. Light in the environment can have extensive effects on specific brain functions. As an important physical modality treatment method, light therapy is a novel intervention that has several strengths: non-invasive, safe, effective, low-cost, few adverse effects, and high compliance. It has clear advantages in terms of tolerance and safety. Light therapy has significant clinical values in the rehabilitation field of brain function modulation. This study systematically reviews the application of light therapy in the rehabilitation of mood disorders, cognitive dysfunction, sleep disorders, and pain. The results support that light therapy exerts a positive regulatory effect on various diseases related to brain function. However, the application of light therapy in brain function modulation is still in its early stage and there are several limitations. For example, the specific mechanisms of light therapy need to be further clarified, there is a lack of research on the combined use of light therapy with other treatments, and the long-term clinical effects remain to be observed. Future research should focus on analyzing the neural mechanisms of light therapy, establishing new intervention paradigms that target specific neural circuits and efficiently modulate brain function, and exploring whether light therapy can produce additional rehabilitative outcomes when combined with traditional treatments. Additionally, long-term follow-up studies are needed to observe the lasting effects of light therapy and to provide valuable insights for its application in brain function modulation.